Type and Linguistic Form of Register Used for Online Buying and Selling on Shopee Live - Kharisma Atika Kirani; Sutopo, Anam (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
Language variation in specific social settings, known as register, is a vital area of sociolinguistics that reflects the dynamic nature of communication. This study investigates the types of registers and their linguistic forms used in Shopee Live, a real-time e-commerce platform that enables direct interaction between sellers and buyers. Unlike previous studies that focused on static online platforms, this research explores the spontaneous and interactive nature of live streaming commerce. A descriptive qualitative method was employed to analyze the utterances from four skincare online shops during Shopee Live sessions. The data were collected through observation, transcription, and interviews, and validated using source and technique triangulation. The analysis applied Martin Joos’s theory of register types and Halliday’s theory of situational context. The findings reveal two types of register used: consultative (17 data) and casual (19 data), with the casual register being more dominant. Consultative registers typically appeared in semi-formal buyer-seller exchanges and used nouns and verbs to deliver product information professionally. Casual registers were characterized by informal expressions, simple noun phrases, and emotional or persuasive language aimed at engaging viewers. The dominance of the casual register reflects the sellers' strategy to build closeness with buyers while maintaining informative content through the consultative register. This study highlights how sellers adjust their linguistic choices to suit the communicative needs of the Shopee Live environment, balancing professionalism and friendliness to optimize buyer engagement.